A history of Old English literature - Fulk, R. D. (Robert Dennis) (Blackwell histories of literature., 2013)
This revised edition of A History of Old English Literature draws extensively on the latest scholarship to have evolved over the last decade. The text incorporates additional material throughout, including two new chapters on Anglo-Saxon manuscripts and incidental and marginal texts. This revised edition responds to the renewed historicism in medieval studiesProvides wide-ranging coverage, including Anglo-Latin literature as well as non-canonical writingsIncludes new chapters on manuscripts and on marginal and incidental textsIncorporates expande.